2018
DOI: 10.1101/377408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying the cognitive processes underpinning hippocampal-dependent tasks

Abstract: Autobiographical memory, future thinking and spatial navigation are critical cognitive functions that are thought to be related, and are known to depend upon a brain structure called the hippocampus. Surprisingly, direct evidence for their interrelatedness is lacking, as is an understanding of why they might be related. There is debate about whether they are linked by an underlying memory-related process or, as has more recently been suggested, because they each require the endogenous construction of scene ima… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 90 publications
2
15
0
Order By: Relevance
“…A limitation to these findings is the use of self-report, although our navigation measure corresponds to performance-based measures (Selarka et al, 2019). Moreover, our findings are in accord with those reported in relation to spatial navigation performance (Clark et al, 2019), and AUTOBIOGRAPHICAL EPISODIC MEMORY AND NAVIGATION 16 we conducted detailed control analyses to rule out several alternative explanations, such as an overall social desirability bias in self-report (supplemental materials). Another caveat to our interpretation is that our measure of navigation ability focused on navigating familiar environments, whereas the cognitive map theory literature largely studies new-route-learning; and the OSIQ-object scale focuses on measuring imagery vividness, while scene construction theory also emphasizes the coherent integration of scene components.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…A limitation to these findings is the use of self-report, although our navigation measure corresponds to performance-based measures (Selarka et al, 2019). Moreover, our findings are in accord with those reported in relation to spatial navigation performance (Clark et al, 2019), and AUTOBIOGRAPHICAL EPISODIC MEMORY AND NAVIGATION 16 we conducted detailed control analyses to rule out several alternative explanations, such as an overall social desirability bias in self-report (supplemental materials). Another caveat to our interpretation is that our measure of navigation ability focused on navigating familiar environments, whereas the cognitive map theory literature largely studies new-route-learning; and the OSIQ-object scale focuses on measuring imagery vividness, while scene construction theory also emphasizes the coherent integration of scene components.…”
Section: Discussionsupporting
confidence: 65%
“…Aydin (2018) found that object imagery was related to AUTOBIOGRAPHICAL EPISODIC MEMORY AND NAVIGATION 15 phenomenological characteristics such as the level of sensory and perceptual details retrieved in relation to past experiences, whereas spatial imagery predicted the level of episodic specificity of past events. Clark et al (2019) reported that navigation performance dissociated from autobiographical memory retrieval and scene construction, and they speculated that navigation reflects schematic, spatial imagery whereas autobiographical memory draws upon vivid imagery for objects and scenes. Our present findings support this contention: vivid object imagery was associated with rich self-reported episodic autobiographical memory, while spatial imagery tapped into the relatively independent construct of navigational ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, scenes are a highly efficient means of packaging information. Clark et al (2019) recently reported that the ability to construct scene imagery explained the relationships between episodic memory, imagining the future and spatial navigation task performance. The prominence of scenes was further emphasised in another study involving the same sample, where the explicit strategies people used to perform episodic memory recall, future thinking and spatial navigation tasks was assessed (Clark, Monk, & Maguire, preprint).…”
Section: The Hippocampus Is Upregulated During Scene Processingmentioning
confidence: 99%